Sex-specific temporal trends in the incidence of atrial fibrillation in a large Norwegian population-based study 1986–2014. (25th November 2020) - Sharashova, E; Wilsgaard, T; Ball, J; Gerdts, E; Rosengren, A; Njolstad, I; Mathiesen, E.B; Schirmer, H; Nyrnes, A; Kildal, S; Tiwari, S; Espnes, H; et al.
Abstract: Background: Due to population aging, increasing prevalence of obesity and enhanced detection, the prevalence of atrial fibrillation (AF) worldwide is increasing steadily. Considerable sex differences in the epidemiology of AF such as lower prevalence and later onset in women compared to men have been reported. However, little is known about sex-specific temporal trends in AF incidence within the general population. Purpose: To explore sex-specific age-adjusted secular trends in the incidence of AF in a general population from Norway between 1986 and 2014. Methods: A total of 16, 865 men and 15, 413 women aged 20 years or older and without AF were enrolled in a longitudinal population study between 1986 and 2008 and followed up for incident AF to the end of 2014. Follow-up was from the date of attendance to the date of AF, emigration or death, whichever came first. All AF cases were validated by an independent endpoint committee using hospital and death records. AF incidence rates were calculated for each calendar year by dividing the number of AF cases per year by the corresponding person-time at risk. To allow for non-linear time trends, calendar year was fitted using fractional polynomials. Poisson regression was used to estimate calendar year-specific AF incidence rates adjusted for age. All analyses were stratified by sex. Results: A total of 911 AF events in women and 1, 139 AF events in men occurred over 324, 090 person-years and 294, 531 person-years of follow-up, respectively. During the study period AF incidence rates in men were at least double that in women (Figure). Age-adjusted AF incidence rates in women increased from 1986, peaked at 0.87 per 1000 person-years in 1998 and then decreased slightly towards 2014. In men AF incidence rates increased up to 2.18 per 1000 person-years in 2005 and then steeply decreased. Conclusion(s): AF incidence rates decreased in both women and men towards the end of the study period. The decrease was more profound in men compared to that in women. One possible explanation is more pronounced reduction in incidence and better treatment of myocardial infarction in men compared to women given that the aetiology of AF in men is mainly ischemic heart disease-related. However, further epidemiological analyses should be undertaken to identify explanatory factors. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): University Hospital of North Norway, Northern Norway Regional Health Authority